Experimental investigation of strength properties of concrete with partial replacement of cement with glass powder and fine aggregate with foundry sand (International Journal of Engineering and Computer Science, 2017)
Management of natural income and preservation of environment is necessary thing. Rapid growth of industrialization has resulted the production of huge volume of wastes, equally in solid and liquid in manufacturing zones. It’s apparent that around 10- 15% of wastes formed are hazardous and creation of hazardous wastes is increasing at the rate of 2-5% per year. These generated waste were dumped on land or discharged in to water bodies and thus becomes a large source of environment pollution and wellbeing threats. This study grants the evidence about use of industrial wastes as a suitable material for construction purposes, by which cost of construction can be condensed and also a safe disposal of waste materials can be achieved. In the present study cement will be partly replaced by glass fine particles (5%, 10%, 15%, and 20%) and fine aggregates will be partially replaced by foundry sand (5%, 10%, 15%, and 20%). The strength factors such as compressive strength, split tensile strength will be conducted for both 7 days and 28 days of curing period. Based on the test results suitable proportion of substitution will be decided.